1996
DOI: 10.1007/bf00157684
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of 72 kDa type IV collagenase (MMP-2) in human malignant gliomas in vivo

Abstract: The 72 kDa type IV collagenase (gelatinase), a matrix metalloproteinase (MMP-2), has been proposed to potentiate the invasion and metastasis of malignant tumors. To determine the potential role of the MMP-2 in human gliomas and normal brain tissue, we examined the relative amounts of protein, mRNA, and distribution. Using gelatin zymography, densitometry, and an enzyme-linked immunosorbent assay for the quantitative determination of the MMP-2, we found that the enzyme's activity was significantly elevated in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
1
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(125 citation statements)
references
References 26 publications
(29 reference statements)
11
108
1
2
Order By: Relevance
“…39 Other studies have demonstrated that high levels of b1 integrin subunit are expressed in glioma cells, 31 and stimulation of the b1 integrin subunit increases the activation of MMP-2, which is the most crucial proteinase in the invasiveness of glioma cells. [40][41][42][43][44] We reported that cells migrating from malignant glioma spheroids can be stained with anti-MMP-2 antibody, despite poor staining of the spheroid itself. 30 We have not fully clarified the biologic mechanism through which glioma cell motility is suppressed by the downregulation of laminin a4 chain expression.…”
Section: Discussionmentioning
confidence: 99%
“…39 Other studies have demonstrated that high levels of b1 integrin subunit are expressed in glioma cells, 31 and stimulation of the b1 integrin subunit increases the activation of MMP-2, which is the most crucial proteinase in the invasiveness of glioma cells. [40][41][42][43][44] We reported that cells migrating from malignant glioma spheroids can be stained with anti-MMP-2 antibody, despite poor staining of the spheroid itself. 30 We have not fully clarified the biologic mechanism through which glioma cell motility is suppressed by the downregulation of laminin a4 chain expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, recombinant or over-expressed TIMP-4 had no effect on cellular viability and proliferation (as measured by 3 H-thymidine incorporation and MTT assays, data not shown), but substantially reduced the invasive capacity of glioma cells through Matrigel. Several MMPs have been linked with the invasive behaviour of malignant gliomas, including MMP-2, MMP-9 and MT1-MMP (Saxena et al, 1995;Sawaya et al, 1996;Uhm et al, 1996;Yamamoto et al, 1996;Deryugina et al, 1998;Lampert et al, 1998;Belien et al, 1999;Forsyth et al, 1999;Price et al, 1999;Raithatha et al, 2000). In particular there is growing evidence for involvement of several other members of the MT-MMP family including MT2-MMP (Nakada et al, 1999), MT5-MMP (Llano et al, 1999) and MT6-MMP (Velasco et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Co-cultures of brainderived human fibroblasts involving interactions with glioblastoma cells induced production and activation of matrix metalloproteinase MMP2, and its activators MT1-MMP and MT2-MMP (Sameshima et al, 2000). These metalloproteinases have all been shown to be involved in the progression of gliomas (Belien et al, 1999;Sawaya et al, 1996;Uhm et al, 1996).…”
Section: Fibroblasts In the Brain Tumor Microenvironmentmentioning
confidence: 99%